Effects of proprioceptive training in the recovery of patients submitted to meniscus surgery: systematic review and meta-analysis - Song Jin; Xiaoxiao Liu; Di Zhang; Ju Wang; Tianyu Zhao; Jiang Ma; Huaimin Lu (BMJ Open)
Objective To evaluate the effects of proprioceptive training on rehabilitation of knee after arthroscopic partial meniscectomy (APM).Design PubMed, EMBASE, The Cochrane Library, Web of Science, China National Knowledge Infrastructure, Technology Periodical Database, WanFang Data and China Biology Medicine were searched until December 2021 for randomised controlled trials.Participants Patients who have undergone APM for meniscus injury caused by traumatic tear.Results A total of 9 studies with 453 patients were included in this study for meta-analysis, and 2/9 with high quality, 6/9 with moderate quality. Based on very low quality evidence, the pooled effect showed significant improvement for proprioceptive training group in proprioception test (p<0.05, I2=18%), knee extensor muscle strength (p<0.05, I2=29%), knee flexor muscle strength (p<0.05, I2=0%) and knee function score (p<0.05, I2=0%) compared with conventional training group in patients after APM.Conclusion Based on very low quality, adding proprioceptive training to conventional rehabilitation programmes might be beneficial to promote functional recovery for patients after APM. It is necessary to carry out more samples and higher quality large-scale studies to provide high evidence in the future.PROSPERO registration number CRD42020213201.